A rare cause of bilateral sudden deafness. (August 2017) - Vos, FI; Merkus, P; van Nieuwkerk, EBJ; Hensen, EF
Abstract : Introduction: Diagnostic delay in relapsing polychondritis (RP) is in part explained by the fact that, by definition, the disease has to relapse before the diagnosis can be made, but also by its pluriform clinical presentation: auricular chondritis, arthritis and respiratory tract involvement are the most common signs in RP. Sensorineural hearing loss and vestibular dysfunction, as observed in the case we will describe, are less common, and facial nerve involvement is rare. Furthermore, this case is one of very few in which a cochlear implant was indicated after sudden deafness caused by RP. Case description: In this case, we describe a 62-year-old female with recurring episodes of sudden deafness, vertigo and facial paresis. Within a month's time, this resulted in bilateral deafness and vestibular areflexia. Erroneously, the patient was diagnosed and treated as having sudden deafness of unknown origin and subsequently neuroborreliosis (Lyme disease). The true diagnosis of RP was revealed 9 months after initial presentation after the patient was referred to our department for cochlear implantation. At this time, an episode of a red and swollen ear occurred, which prompted further examination and subsequent diagnosis. During cochlear implantation, the base of the cochlea was found to be partially calcified. Insertion and hearing rehabilitation were however successful. Results and conclusions: Timely identification of RP as the cause of this profound sensorineural hearing loss proved to be important. Not only in order to provide suitable follow-up, but because of the risk of cochlear obliteration, which had already begun in our patient and might have hampered optimal hearing rehabilitation. Our recommendation is to urgently refer any patient with bilateral sudden deafness to a cochlear implant center, especially when signs of postinflammatory calcification of the cochlea are identified, like it was in this case of RP. Take-home message: Due to the pluriform presentation and relapsing nature of RP, patients almost never present with the 'full clinical picture' of RP. Because of this, different doctors of different disciplines (mostly general practitioners, otolaryngologists, ophtalmologists and rheumatologists) see different symptoms at different moments in time. Frequently, symptoms have initially been attributed to other forms of disease, and only careful history taking with attention to symptoms beyond the scope of one's own specialty, will reveal the diagnosis.